Optimizing Arabic Language Assessment through Anates Analysis - Haq, Alfa Izzul; Anwar, Najih (Universitas Muhammadiyah Sidoarjo, 2024)
This study evaluates the quality of Arabic Language questions in a Mid-Semester Summative Assessment using the Anates V4.0.9 program. Employing a descriptive quantitative approach, 20 multiple-choice questions were administered to 30 class 10 students at SMA Muhammadiyah 2 Sidoarjo. Results indicate an 80% validity rate, with a reliability coefficient of 0.87, suggesting consistency. The questions demonstrate a medium level of difficulty and an 80% discriminating power, effectively distinguishing between students' understanding levels. These findings underscore the importance of rigorous assessment practices in Arabic Language education, aiding educators in enhancing assessment quality and improving student learning outcomes. Highligh: Assessment: Anates V4.0.9 Program for Arabic Language Questions Analysis. Student Understanding: 80% Question Discrimination Highlights Assessment Precision. Educational Insights: Enhancing Arabic Language Assessment for Optimal Learning Outcomes. keywoard: Arabic Language Assessment, Validity, Reliability, Difficulty Level, Distinguishing Power